2016
DOI: 10.12775/aunc_econ.2016.006
|View full text |Cite
|
Sign up to set email alerts
|

Uwarunkowania źródeł finansowania inwestycji infrastruktural-nych w gminach województwa małopolskiego

Abstract:  Publikacja została dofinansowana ze środków przyznanych Wydziałowi Ekonomii i Stosunków Międzynarodowych Uniwersytetu Ekonomicznego w Krakowie w ramach dotacji na utrzymanie potencjału badawczego w 2016 roku.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent experience has shown that the attempts to create synthetic measures of development and to build multi-component indicators, as well as objectified measures of economic phenomena (Dziekański, 2014a;Dziekański, 2013;Kik & Nalepka, 2016;Stasiak & Janiszewska, 2019) are relatively frequent. These solutions have both advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experience has shown that the attempts to create synthetic measures of development and to build multi-component indicators, as well as objectified measures of economic phenomena (Dziekański, 2014a;Dziekański, 2013;Kik & Nalepka, 2016;Stasiak & Janiszewska, 2019) are relatively frequent. These solutions have both advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%